2012
DOI: 10.1111/j.1530-9290.2011.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Allocation in Life Cycle Assessment

Abstract: This article examines methods for analyzing allocation in life cycle assessment (LCA); it focuses on comparisons of economic allocation with other feasible alternatives. The International Organization for Standardization's (ISO) guideline 14044 indicates that economic allocation should only be used as a last resort, when other methods are not suitable. However, the LCA literature reports several examples of the use of economic allocation. This is due partly to its simplicity and partly to its ability to illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(73 citation statements)
references
References 46 publications
1
71
0
1
Order By: Relevance
“…This distinction is echoed on websites that track metal prices, such as Reuters and InfoMine. Even with uncertain definitions, the concept of high and low values provides useful guidance when choosing an allocation approach (Ardente and Cellura 2012).…”
Section: Methods To Deal With Co-products For Metalsmentioning
confidence: 99%
“…This distinction is echoed on websites that track metal prices, such as Reuters and InfoMine. Even with uncertain definitions, the concept of high and low values provides useful guidance when choosing an allocation approach (Ardente and Cellura 2012).…”
Section: Methods To Deal With Co-products For Metalsmentioning
confidence: 99%
“…It has been concluded that in most cases allocation cannot be entirely avoided by subdivision and system expansion [19], but can be problematic since it does not consider in how far the change in amount of co-products affects the output of the process [20]. Concerning allocation the pros and cons of physical vs. economic allocation have been the subject of an extensive discussion, which was conveniently summarized by [21]. [22] concludes that wherever physical causalities between functional units exist, allocation should be based on these causal relationships, however, that in some cases socio-economic demands are the driving force behind multiple-functions systems and therefore economic indicators best reflect the changes in the unit processes.…”
Section: Allocationmentioning
confidence: 99%
“…These prices are available on brokerage sites such as RISI (www.risiinfo.com). It is possible to make a mistake by not applying the economic allocation to the right point (Ardente and Cellura 2012). Because this is a gate-to-gate LCA, distribution impacts are not considered.…”
Section: Sensitivity Analysis Of Allocation Approachmentioning
confidence: 99%